Resource curse or debt overhangs? - Manzano, Osmel (2001)
has been widely believed that resource abundant economies grow less that other economies. In a very influential paper, Sachs and Warner (1997), point out that there is a negative relationship between resource abundance and growth. Two important econometric problems are present in the traditional empirical literature: First, the result might depend on factors that are correlated with primary exports but that have been excluded from the regression. Second, total GDP includes the production in the resource sector that has been declining in the last 30 years. We correct for those issues. Our results indicate that the so called “Natural Resource Curse” might be related to a debt overhang….